Risky move: New evidence on the determinants of the willingness to migrate - Johnes, Geraint (REGION, 2020)
Data from a bespoke Totaljobs survey of workers in the UK are used to revisit issue of workers’ willingness to migrate in order to enhance their career opportunities. Demographic variables such as age, gender, and family circumstances are found to have high explanatory power. Education is also an important cofactor, as is the individual’s current income – though the latter has a highly nonlinear effect. Workers located in the north east – a region relatively remote from other large population centres, and one with a strong and distinct cultural identity – are significantly less likely to express a willingness to move. The paper is novel in two respects: in identifying the role played by individual income in mobility, and in allowing for the potential endogeneity of variables associated with attitudes to risk-taking.